A modularized framework for sales and operations planning with focus on process industries. Issue 1 (1st January 2016) - Noroozi, Sayeh; Wikner, Joakim
Abstract : This paper suggests a modularized sales and operations planning (S&OP) framework, consisting of content and process. The framework's content is based on a typology of decoupling points in which the effect of decoupling points on the decision variables in S&OP is studied. The framework's process takes a step back and addresses the need for a more elaborate design to precede the operational use of S&OP content for different production contexts. The framework supports both process industries (PIs) and discrete manufacturing industries (DIs), and recognizes their specific requirements and reflects them in their S&OP. The differentiating characteristics of PIs and DIs are emphasized through three different decoupling points, namely: discretization decoupling point, control mode decoupling point, and customer order decoupling point. The suggested framework aims to fill the gap in the literature regarding the lack of aggregate planning processes that match the PIs' specific requirements by reflecting the differentiating characteristics of PIs in S&OP.